2021
DOI: 10.1021/acs.jpcc.1c02363
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Water–Gas Shift Catalysts for H2O and CO Dissociation Using Cu–Ni Step Alloy Surfaces

Abstract: H2O dissociation is the rate-limiting step for the water–gas shift (WGS) reaction. Density functional theory (DFT) was used to study H2O and CO dissociation on a series of step (211) bimetallic alloy surfaces consisting of Cu and Ni metals. The water dissociation process was more facile on (211) step surfaces than on (111) flat surfaces. But CO dissociation on the (211) step surfaces was less reactive than that on its close-packed (111) counterparts. Depending on the initial-state structures, the transition st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…The band gap of Ru 1 /V Co -Co­(OH) 2 was 0.26 eV, which was narrower than that of Ru 1 /Co­(OH) 2 (0.62 eV). The narrower band gap of Ru 1 /V Co -Co­(OH) 2 indicated that the existence of neighboring Co 2+ vacancies enhanced the electronic conductivity, which facilitated charge transfer and OER dynamics. …”
Section: Results and Discussionmentioning
confidence: 99%
“…The band gap of Ru 1 /V Co -Co­(OH) 2 was 0.26 eV, which was narrower than that of Ru 1 /Co­(OH) 2 (0.62 eV). The narrower band gap of Ru 1 /V Co -Co­(OH) 2 indicated that the existence of neighboring Co 2+ vacancies enhanced the electronic conductivity, which facilitated charge transfer and OER dynamics. …”
Section: Results and Discussionmentioning
confidence: 99%
“…In addition, Cu and Ni were reported to be effective catalysts for H 2 O dissociation in WGSR. [28][29][30] Gan et al [31] demonstrated that loading Ni in Cu to form NiCu bimetallic can improve H 2 O dissociation, where Ni can help break the bond of C≡O and promote methane yield. Knudsen et al [32] found that improving Cu by using Cu/Pt nearsurface alloy can easily activate H 2 O, adsorb the products weakly, and avoid poisoning during the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Cu and Ni were reported to be effective catalysts for H 2 O dissociation in WGSR. [ 28–30 ] Gan et al. [ 31 ] demonstrated that loading Ni in Cu to form NiCu bimetallic can improve H 2 O dissociation, where Ni can help break the bond of C≡O and promote methane yield.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] In this regard, CuNi alloy nanoparticles have become popular in research area for superior catalytic applications mainly due to formation of solid solutions as both metals have similar atomic radii, structures and electronegativities. 31 Furthermore, modern studies reveal that carbon coated nanoalloy composites are good enough to fabricate the electrode material with appropriate catalytic properties, especially, multiwall carbon nanotubes (MWCNTs), that have specific mesoporous architecture, enhanced catalytic surface area, excellent chemical stability and good electrical conductivity. Moreover, MWCNTs may enhance the electron transfer kinetics for the process of charge/discharge.…”
Section: Introductionmentioning
confidence: 99%